Communicating fundamentals of water and sanitation in Moslem communities - Yacoob, May (Journal of religion and health, 1985)
According to the World Health Organization, 80 percent of all human diseases in the Third World relate to inadequate sanitation and the lack of clean water. Moreover, the incidence of these water-borne diseases shows no sign of-diminishing, despite the installation of improved water systems in many rural communities. The beneficiaries of these systems, and particularly the women, remain as unaware of the benefits of improved water use and sanitation practices as they are of the germ theory of disease causation. Accordingly, this paper suggests the use of a community's existing values and belief structures in developing a strategy for communicating the need of behavioral change in water and sanitation practice. The author discusses how Koranic religious values can help promote this change, and suggests an operational strategy for use by international agencies in Moslem communities.